2001
DOI: 10.1128/aem.67.3.1070-1075.2001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Agrobacterium tumefaciens attR Mutation on Attachment and Root Colonization Differs between Legumes and Other Dicots

Abstract: Infections of wound sites on dicot plants by Agrobacterium tumefaciens result in the formation of crown gall tumors. An early step in tumor formation is bacterial attachment to the plant cells. AttR mutants failed to attach to wound sites of both legumes and nonlegumes and were avirulent on both groups of plants. AttR mutants also failed to attach to the root epidermis and root hairs of nonlegumes and had a markedly reduced ability to colonize the roots of these plants. However, AttR mutants were able to attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…A 30-kb cluster of A. tumefaciens att genes has also been described as being required for attachment and tumorigenesis (316,317,319). However, the recently published A. tumefaciens genome sequence revealed that the att genes are located on the cryptic plasmid pAtC58, which is not essential for virulence (233,423).…”
Section: Binding To Host Surfacesmentioning
confidence: 99%
“…A 30-kb cluster of A. tumefaciens att genes has also been described as being required for attachment and tumorigenesis (316,317,319). However, the recently published A. tumefaciens genome sequence revealed that the att genes are located on the cryptic plasmid pAtC58, which is not essential for virulence (233,423).…”
Section: Binding To Host Surfacesmentioning
confidence: 99%
“…Mort and Grover (1988), studying the sugar composition of RH cell walls, demonstrated that among legumes, the RH carbohydrate composition did not differ much; on the contrary, there was a large variation when legumes were compared with nonlegumes. This difference among families was further emphasized by Matthysse and McMahan (2001) who studied the attachment of Agrobacterium tumefaciens to RH. AttR mutants of Agrobacterium tumefaciens are able to differentiate RH of nonlegumes from those of legumes; the bacterium is unable to attach to the former whereas it binds to the latter (Matthysse and McMahan 2001).…”
Section: Mode Of Entry Determined By the Plantsmentioning
confidence: 99%
“…This difference among families was further emphasized by Matthysse and McMahan (2001) who studied the attachment of Agrobacterium tumefaciens to RH. AttR mutants of Agrobacterium tumefaciens are able to differentiate RH of nonlegumes from those of legumes; the bacterium is unable to attach to the former whereas it binds to the latter (Matthysse and McMahan 2001). Since Agrobacterium is closely related to Rhizobium (Young and Johnston 1989), especially Rhizobium leguminosarum and Rhizobium meliloti, it is plausible to assign a similar behaviour to Rhizobium.…”
Section: Mode Of Entry Determined By the Plantsmentioning
confidence: 99%
“…Bacteria associated with plants frequently form biofilms on leaves, on root surfaces, and within the intercellular spaces of plant tissues (1,3,5,13,34,38,43). Microscopic studies show that the rhizobial cells migrate down the infection threads as biofilm-like filaments toward the root interior (15,43).…”
mentioning
confidence: 99%